2015
DOI: 10.1371/journal.pone.0138849
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Starvation in Cardiomyocytes Enhances Exosome Secretion and Promotes Angiogenesis in Endothelial Cells

Abstract: Cardiomyocytes (CMs) and endothelial cells (ECs) have an intimate anatomical relationship that is essential for maintaining normal development and function in the heart. Little is known about the mechanisms that regulate cardiac and endothelial crosstalk, particularly in situations of acute stress when local active processes are required to regulate endothelial function. We examined whether CM-derived exosomes could modulate endothelial function. Under conditions of glucose deprivation, immortalized H9C2 cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 47 publications
6
139
0
2
Order By: Relevance
“…Bhattacharyya et al [15] found that hyperglycemia-induced tumor growth of breast cancer was impaired by inhibition of angiogenesis, indicating that angiogenesis induced by hyperglycemia was correlated with breast cancer. Garcia et al [16] demonstrated the role of angiogenesis in heart diseases by promoting the angiogenesis of rat cardiomyocytes by glucose starvation. In our research, we found that high glucose could promote the angiogenesis of RF/6A cells, which may be involved in the pathological processes of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Bhattacharyya et al [15] found that hyperglycemia-induced tumor growth of breast cancer was impaired by inhibition of angiogenesis, indicating that angiogenesis induced by hyperglycemia was correlated with breast cancer. Garcia et al [16] demonstrated the role of angiogenesis in heart diseases by promoting the angiogenesis of rat cardiomyocytes by glucose starvation. In our research, we found that high glucose could promote the angiogenesis of RF/6A cells, which may be involved in the pathological processes of DR.…”
Section: Discussionmentioning
confidence: 99%
“…Gene Ontology (GO) analysis of exosome cargo identified the molecules, which alters the angiogenic activity of the endothelial cells. In glucose deprived medium, the exosomes were identified to be loaded with functional glucose transporters and glycolytic enzymes, which are internalized by ECs to increase glucose uptake, glycolytic activity, and pyruvate production in recipient cells 27,109 . A paracrine miRNA crosstalk between cardiac fibroblasts (CFs) and cardiomyocytes (CMs) was found to be mediated by the CF secreted miRNA-enriched exosomes.…”
Section: Therapeutic Effects Of Exosomes Derived From the Differenmentioning
confidence: 99%
“…Additionally, miR-451 was shown to be enriched in EVs from other cells including normal cells (Collino et al 2010; Guduric-Fuchs et al 2012; Pigati et al 2010) in contrast to miR-21, calling into question the specificity of action that this microRNA may exert on microglia. Finally, the analysis of transcriptional regulation (primary transcript) of microRNA-451 in recipient cells may shed new light on a described mode of action, as this particular microRNA was found to be dramatically deregulated upon exposure to stress (Ansari et al 2015; Godlewski et al 2010b) and stress also is an additional mechanism of EV secretion/loading (de Jong et al 2012; Garcia et al 2015; Yu et al 2006). The finding that microRNAs naturally enriched in EVs are post-transcriptionally regulated (Koppers-Lalic et al 2014) questions whether such modification (uridylation of 3′ end of microRNA) has an impact on the affinity of target recognition.…”
Section: Micrornas In Brain Tumorsmentioning
confidence: 99%